Al-Hakim al Tirmidhi and Teresa of Avila: The Seven Stage Journey of the Soul and Spiritual Direction - Philips, Gerardette (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2019)
The core feature of the spiritual life is human and divine desiring. Understanding and facing our desires as well as comprehending the desires of the Divine, remain a struggle for the human soul. Spiritual directors are likely to spend a considerable amount of time on this struggle and need to develop great skill in recognizing and responding to their directees’ desire for God and in helping them discern and unveil the illusory desires. This article explores the theories and insights of the spiritual stage theory from Islam through Sufism using the psychology of Al-Hakim al Tirmidhi and Christianity through Teresa of Avila, and the spiritual direction best suited for spiritual directees at the different stages. The exchange of both of these approaches presented here can perhaps enrich the spiritual directors’ style to travellers along the spiritual journey who come to them for direction. This mystical spirituality, articulated in Sufism from the Stations (maqamat) of Hakim Al-Tirmidhi and the mansions of Teresa of Avila, though experienced within different spiritual frameworks, brings a commonality in the exchange between them. Their experience of God both as directees and as Shaykh or Spiritual Director has much to offer to present day spiritual directors.